A special single variant zone in directionally solidified Ni-Mn-Ga alloy. (1st July 2019) - Dai, Yanchao; Hou, Long; Chulist, Robert; Fautrelle, Yves; Li, Zongbin; Yang, Bo; Esling, Claude; Ren, Zhongming; Li, Xi
Abstract: Three distinct structures comprising self-accommodated solid zone, (110)M preferred oriented liquid zone and (001)M oriented single variant zone were discovered in directionally solidified Ni-Mn-Ga alloy rod. The preferred (110)M orientation in liquid zone directly causes a special single variant zone to form around quenching interface. It is attributed to a longitudinal, suddenly-shrinking lattice, produced in the liquid zone after martensitic transformation, which induces a tension force at the joint. A tensile test simulates and validates the formation of single variant induced by inner force. A mechanism of variant formation is described in the present study, too. Graphical abstract: Unlabelled Image